Gas Chromatography Analysis of Discharge Products in N2‐CH4 Gas Mixture at Atmospheric Pressure: Study of Mimic Titan's Atmosphere. Issue 6 (1st April 2015) - Torokova, L.; Watson, J.; Krcma, F.; Mazankova, V.; Mason, N. J.; Horvath, G.; Matejcik, S.
Abstract In this paper, we report presence of various organic products formed in a flowing atmospheric glow discharge fed by gas mixture containing 1‐5 % of methane in nitrogen, which mimics the Titan's atmosphere. Gaseous products from the discharge exhaust were analysed by Gas Chromatography with Mass Spectrometry (GC‐MS). The experimental results revealed C2H2, HCN, and CH3CN as the major products. Various hydrocarbons and nitriles were the other determined gaseous products. Whilst many of these compounds have been predicted and/or observed in the Titan atmosphere, the present plasma experiments provide evidence of both the chemical complexity of Titan atmospheric processes and the mechanisms by which larger species grow prior to form the dust that should cover much of the Titan's surface. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)